2001
DOI: 10.1111/j.1349-7006.2001.tb01176.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Formation of Azoxymethane‐induced Colorectal Adenocarcinoma in γδ T Lymphocyte‐deficient Mice

Abstract: γδ T cells have been reported to secrete a cytokine which supports the elimination of impaired epithelial cells and to maintain the normal configuration of the intestinal epithelium. 5,6) However, the precise functions of γδ T cells have not been elucidated. Some recent studies have described the effect of γδ T cells on intestinal tumor cells. γδ T cells regulated the cytotoxic activities of NK cells and CTL, of which the targets were intestinal tumor cells.7) The frequency of tumorinfiltrated γδ T cells was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
3
18
0
Order By: Relevance
“…Our findings are in line with reports of a peripheral gd T cell deficit in patients with other types of malignancies such as cutaneous primary melanoma (68) and nasopharyngeal carcinoma (70). The possibility that low levels of circulating gd T cells may contribute to the failure of immune surveillance against AML is supported by studies of gd T lymphocyte-deficient mice: These animals are highly susceptible to cutaneous carcinogenesis (72) and colorectal adenocarcinoma can be readily induced (69). Similarly, gd T lymphocyte-deficient mice targeted with pathogenic and nonpathogenic insults are susceptible to severe tissue damage and unimpeded bacterial growth (73).…”
Section: Flow Cytometric Assessment Of CD T Cells In Amlsupporting
confidence: 79%
See 1 more Smart Citation
“…Our findings are in line with reports of a peripheral gd T cell deficit in patients with other types of malignancies such as cutaneous primary melanoma (68) and nasopharyngeal carcinoma (70). The possibility that low levels of circulating gd T cells may contribute to the failure of immune surveillance against AML is supported by studies of gd T lymphocyte-deficient mice: These animals are highly susceptible to cutaneous carcinogenesis (72) and colorectal adenocarcinoma can be readily induced (69). Similarly, gd T lymphocyte-deficient mice targeted with pathogenic and nonpathogenic insults are susceptible to severe tissue damage and unimpeded bacterial growth (73).…”
Section: Flow Cytometric Assessment Of CD T Cells In Amlsupporting
confidence: 79%
“…We first examined gd T cell levels in AML patients at diagnosis since it has been suggested that the frequency of these cells plays a role in the balance between health and disease (3,67), and that an impairment of T cells expressing g/d TCRs may lead to a downregulation of normal immune defense (68)(69)(70). In this regard, it is of interest that in patients with advanced stage solid tumors a correlation between low gd T cell counts and short survival time has been reported (58).…”
Section: Flow Cytometric Assessment Of CD T Cells In Amlmentioning
confidence: 99%
“…In our studies, the TCRδ −/− B6 mice showed a tumor incidence that was not statistically different from either WT or TCRβ −/− mice treated with AOM + DSS (Table ). In contrast, when TCRδ −/− B6 mice were treated with 5 weekly injections of 10 mg/kg AOM (without DSS) the tumor incidence was 50% at 7 months, while WT and TCRα −/− B6 mice did not develop CRC . B6 mice are relatively resistant to AOM as a single agent; therefore, this result in the TCRδ null animals indicates that γ/δ T‐cells may play a role in the resistance of WT B6 mice to CRC development.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, TCR-␥␦ -deficient mice are susceptible to mutagen -induced local carcinomas [20] and to localized inflammation by toxic chemicals [21]. TCR-␣␤ + CD8␣␣ T-IEL were shown to mimic the role of CD4 + CD25 + regulatory T cells in preventing the colitis induced by injection of CD4 + naïve T cells into T cell -deficient mice; this regulation was demonstrated to be mediated by IL-10 [22].…”
Section: Functions Of Cd8␣␣ T-ielmentioning
confidence: 93%